Pemanfaatan Abu Batu Untuk Bahan Bangunan Batako, Paving Block Dan Roster - H. Listiawaty; I. K. Sulendra; T. Hilmansyah; M. Sutrisno (CV. Multi Kreasi Media, 2023)
Central Sulawesi is one of the main producers of Quarry C, which is processed into crushed stone in crushed stone factories (stone crushers). The number of crushed stone factories operating in the area between Palu-Donggala City is around forty units. The production of crushed stone factories apart from 1-2